2011
DOI: 10.1097/ppo.0b013e31820a0948
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Treatment Response After Nonoperative Therapy for Early-Stage Non-Small Cell Lung Carcinoma

Abstract: Nonsurgical management of early primary lung cancer has grown tremendously in recent years, and today, available options extend far beyond that of conventional radiation therapy (CRT) to include minimally invasive image-guided delivery of thermal energies, specifically radiofrequency ablation, microwave ablation, and cryoablation, and more conformal stereotactic body radiation therapy. Because the tumor is never resected with these nonoperative interventions, histopathological evaluation of tumor margins for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Distinguishing recurrence in these patients can therefore be challenging and requires experienced readers, also considering the fact that radiation-induced fibrosis can appear more than 1 year after the end of therapy [38]. Detection of recurrence may be difficult within 9 months of the delivery of SBRT because of secondary radiation pneumonitis [39]. Matsuo et al [40] reported that, among other factors, only growth of consolidation after 12 months on CT was a statistically relevant predictor of recurrence.…”
Section: Parenchymal and Bronchial Recurrencementioning
confidence: 98%
See 1 more Smart Citation
“…Distinguishing recurrence in these patients can therefore be challenging and requires experienced readers, also considering the fact that radiation-induced fibrosis can appear more than 1 year after the end of therapy [38]. Detection of recurrence may be difficult within 9 months of the delivery of SBRT because of secondary radiation pneumonitis [39]. Matsuo et al [40] reported that, among other factors, only growth of consolidation after 12 months on CT was a statistically relevant predictor of recurrence.…”
Section: Parenchymal and Bronchial Recurrencementioning
confidence: 98%
“…Matsuo et al [40] reported that, among other factors, only growth of consolidation after 12 months on CT was a statistically relevant predictor of recurrence. Otherwise, other findings already described as signs of recurrence after conventional radiotherapy can be used to suspect recurrence after SBRT; these include the filling of radiation-induced ectatic bronchi [41], development of bulging at margins of radiation-induced consolidation, and [39]. PET-CT is also a helpful technique for early detection of recurrence after SBRT, even though it needs to be applied in conjunction with other techniques [42].…”
Section: Parenchymal and Bronchial Recurrencementioning
confidence: 99%
“…However, Eradat et al in their comprehensive review have stated that 1 week after ablation is too soon to detect treatment response by 18F-FDG PET (Eradat et al 2011). In fact, post-ablation inflammation may obscure subcentimeter residual tissue, and so it is usually delayed until 2 months (Okuma et al 2006).…”
Section: Lung Cancermentioning
confidence: 98%
“…In fact, post-ablation inflammation may obscure subcentimeter residual tissue, and so it is usually delayed until 2 months (Okuma et al 2006). However, during the intermediate phase (1 week to 2 months), a reduction of less than 60 % of uptake relative to pretreatment value is an indicator of persistent disease (Eradat et al 2011).…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation